Molecular Configuration of Gelatin-Water Suspensions at Low Concentration - Melo-Hurtado, F; Caballero-Alvial, L (2014)
Direct assessment of gelatin molecular configuration has been difficult due the complexity of the molecule and limitations of analytical techniques. The objective of this work was the molecular characterization of bovine gelatin as a function of temperature, concentration and time. Diluted suspensions were prepared at different concentrations (7.5×10-5 to 1.5g/l) and kept at temperatures above (S1) (40°C) and below (S2) (5°C) the gelling point as determined by Differential Scanning Calorimetry. Circular dichroism measurements showed the secondary structure of a polyproline II like spectra similar to native collagen at S1 and a denaturated configuration at S2 conditioning. Atomic Force Microscopy (AFM) at S1, using a HOPG substrate, showed single strands segments with two marked distributions in heights, ~0.6nm and ~1.6nm, indicating possible helical configurations even at high temperatures. At S2, AFM showed only one height distribution in the range of ~0.9nm but wider (0.3-1.6nm range). At increasing gelatin concentration (12g/l) and annealing time (48h), a well-defined network was detected with narrow height distribution (~1.0nm) featuring aggregates and highly ordered structure zones. An analysis of gelatin strand interactions, showed a network linked by knots with a coordination number Z=3 (strands) with a bond length of ~50nm. The gel network formation and aggregation was consistent with molecular size increase observed by Dynamic Light Scattering, showing variations in hydrodynamic dimensions from ~10nm (S1) to ~100nm (S2). This experimental approach has allowed to pinpoint differences in molecular configuration of gelatin, which may be applied in the study the structuring pathway of other biopolymers and the association kinetics during storage for a wide range of temperatures. © 2013 Elsevier Ltd.